Slightly photo-crosslinked chitosan/silk fibroin hydrogel adhesives with hemostasis and anti-inflammation for pro-healing cyclophosphamide-induced hemorrhagic cystitis - Jie Yao; Yaoqi Chen; Xiang Zhang; Junfeng Chen; Cheng Zhou; Junhui Jiang; Hua Zhang; Kerong Wu (Materials Today Bio, 2024)
Cyclophosphamide is commonly used in the treatment of various cancers and autoimmune diseases, while concurrently imposing substantial toxicity on the bladder, frequently manifesting hemorrhagic cystitis. Intravesical interventions, such as hyaluronic acid supplementation, present a therapeutic strategy to reinstate bladder barrier function and alleviate the effects of metabolic toxicants. However, it remains a great challenge to achieve efficient cyclophosphamide-induced hemorrhagic cystitis (CHC) management with accelerated tissue repair owing to the low wet-adhesion, poor hemostasis, and acute inflammatory responses. To address these issues, a hemostatic and anti-inflammatory hydrogel adhesive of chitosan methylacryloyl/silk fibroin methylacryloyl (CHMA/SFMA) is developed for promoting the healing of CHC. The obtained hydrogels show a high adhesive strength of 26.21 N/m with porcine bladder, facilitating the rapid hemostasis within 15 s, and reinstate bladder barrier function. Moreover, this hydrogel adhesive promotes the proliferation and aggregation of SV-HUC-1 and regulates macrophage polarization. Implanting the hydrogels into CHC bladders of a SD rat model, they not only can be completely biodegraded in 14 days, but also effectively control hematuria and inflammation, and accelerate angiogenesis, thereby significantly promote the healing of bladder injury. Overall, CHMA/SFMA hydrogels exhibit rapid hemostasis for treating CHC and accelerate muscle tissue repair via angiogenesis and inflammation amelioration, which may provide a new path for managing severe hemorrhagic cystitis in the clinics.